REPRODUKSI KEKERASAN KOLEKTIF: STUDI KASUS KONFLIK AHMADIYAH DI LOMBOK-NTB TAHUN 1998-2006 - , Syaiful Anam; , Dr. Zuly Qodir ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Since the fall of the new order regime in 1998, a series of communal or collective violence occurred in Indonesia with a variety of issues, ranging from political issues, economic, religious, race, and so forth. One of the conflicts that have attracted the attention is about the conflict of Ahmadiyah in Indonesia. This conflict is manifested in the form of collective violence (both physical and non-physical) done by local people and groups of Islamic organizations against citizens of Ahmadiyah Indonesia (JAI), a group of Qadian Ahmadiyah sect. Collective violence spread evenly throughout the areas that have a base of Ahmadiyah Qadian, including the area of Lombok Island, West Nusa Tenggara (NTB). This study aimed to analyze the locality factors (internal) on Lombok which led to collective violence continue to happen over and over since 1998 until 2006. So from this research, we will get a comprehensive and profound understanding of the underlying causes of why conflict of Ahmadiyah happened in Lombok-NTB. This research was conducted using qualitative-exploratory method, through a literature study (library research) and field studies (field research). Research library was done by searching the relevant literature, while the field studies was done by observation and interviews with JAIâs Leader in Lombok, Tuan Guru (ullama), and academics who have studied the Ahmadiyah in Lombok. It was found that the factors that cause reproduction of collective violence toward Ahmadiyah people in Lombok is caused by: the social structure of the Sasak- Lombok people which is difficult to accept the changes